Treatment-induced copper deficiency in two patients with Wilson's disease. Issue 1 (January 2016) - Abdel Ghaffar, Tawhida Y.; Elsayed, Solaf M.; El Naghi, Suzan; Hamed, Hanan; Atta, Huda A.
Abstract : Copper is an essential trace element that is vital to the health of all living cells. However, like all essential elements, its serum level must be kept within normal values; otherwise, conditions of toxicity or deficiency can result, each of which has its own unique set of adverse health effects. Wilson's disease (WD) is an inherited disease of copper accumulation that can cause liver and neurological affection. Its management depends on removal of excess copper using copper chelators such as D-penicillamine or trientine, which increase the urinary excretion of copper. In a more recent approach, zinc has been used to decrease copper accumulation. We present two WD cases that developed copper deficiency as a result of their treatment. These cases improve our understanding and management of copper deficiency in WD and highlight the importance of copper-level monitoring in WD.